Nighttime D-Region Ionosphere Characteristics from Tweek Atmospherics observed in the North America Region - Yusop, Norbayah; Ya’acob, Norsuzila; Mohd Shariff, Khairul Khaizi; Yusof, Azita Laily; Ali, Mohd Tarmizi; Idris, Azlina; Mohd Ali, Darmawaty (2012)
Tweek atmospherics are ELF/VLF pulse signals with frequency dispersion characteristics generate from lightning discharges and spread in the Earth-ionosphere waveguide mode.This study uses the electromagnetic wave approach describe as ELF (extremely low frequency) and VLF (very low frequency)which propagates sub-ionospherically among the earth and the lowest ionosphere. This paper presents the nighttime D-region ionosphere characteristics of tweeks at Gakona station (62.71° N, 143.99°W) in the North America Region. By using the fundamental of cut-off frequency, we estimated the nighttime variations of the tweek reflection height of the D-region ionosphere, equivalent electron density and the distance travel by tweek along its propagation. Our observation indicated that the equivalent electron densities for tweeks varies from 23-27 el/cm3 in the altitude range of 77 to 91 km and demonstrated that these signals is capable to travel up to 5600 km over a wide area in mid-latitude region. Comparison in term of the ionospheric parameters at different latitude shows that the reflection height and electron density in this study is almost consistent for all latitude tweek measurements.